Disaster Mitigation INNOVATION IN MODELLING OF FLOOD-FRIENDLY HOUSING DESIGN WITH APPROACHING OF SUNDANESE TRADITIONAL ARCHITECTURE (Case study: Baleendah Sub-district, Bandung District, West Java-Indonesia) - Nuryanto, Nuryanto Nuryanto; Ahdiat, Dadang; Surasetja, R. Irawan (International Journal of Engineering and Emerging Technology; Vol 4 No 2 (2019): July - DecemberDO - 10.24843/IJEET.2019.v04.i02.p08, 2020)
The research locations are Cieunteung residence in Babakan Mekarsari village and Jambatan village in Andir, Baleendah sub-district, Bandung District-West Java Province in Indonesia. The prototype for flood-friendly houses in villages that will be proposed to the local government. The research gives two important formulas, there are: (1) Concept design of the flood-friendly house with Sundanese architecture approaches (imah panggung) (2) The design of a flood-friendly housing includes: the design of the floor plan, the design of house facade, the design of roof and the design of house structure and construction according to the local wisdom of Sundanese traditional architecture. Two important formulation results in the planning and design ing the flood-friendly houses in the two villages will be submitted as the proposal to the local government as well as consideration to anticipate the wider impact of the flood.